2022
DOI: 10.52965/001c.33696
|View full text |Cite
|
Sign up to set email alerts
|

Lateral extra-articular tenodesis and anterior cruciate ligament reconstruction in young patients: clinical results and return to sport

Abstract: Lateral extra-articular tenodesis (L.E.T.) have been proposed to reduce the tibia’s anterior translation and internal rotation in concomitant to Anterior cruciate ligament (A.C.L.) reconstruction. Recent studies show that the addition of L.E.T. to A.C.L. reconstruction results in a statistically significant reduction in graft failure. The purpose of the present study was to evaluate the clinical outcomes, complications, and rate of return to preinjury sports level in pediatric patients who underwent combined A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Although only used in 26 of 274 knees (9.5%) in this review, concomitant LET procedures are another area of interest in paediatric and adolescent patients undergoing r‐ACLR [47]. The aim of the LET is to reduce anterior translation and internal rotation of the tibia to provide added rotatory stability [48]. Indications for its use include r‐ACLR, high‐grade rotational laxity, and young patients returning to contact pivoting sports [47].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although only used in 26 of 274 knees (9.5%) in this review, concomitant LET procedures are another area of interest in paediatric and adolescent patients undergoing r‐ACLR [47]. The aim of the LET is to reduce anterior translation and internal rotation of the tibia to provide added rotatory stability [48]. Indications for its use include r‐ACLR, high‐grade rotational laxity, and young patients returning to contact pivoting sports [47].…”
Section: Discussionmentioning
confidence: 99%
“…Indications for its use include r-ACLR, high-grade rotational laxity, and young patients returning to contact pivoting sports [47]. Previous studies have shown that performing concurrent LET with ACLR are associated with reduced re-rupture rates [48]. There is a significant positive linear relationship for the number of LETs performed in recent years in light of the growing body of evidence supporting its use in paediatric and adolescent populations [28,48,49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the notable ability to stabilize and even overconstrain the knee, augmented procedures have gained popularity in at-risk patient populations ( 61 , 62 ). These high-risk populations have traditionally included; adolescent patients ( 63 ), revision ACLR ( 64 , 65 ), high grade pivot shift ( 66 ), increased posterior slope ( 67 ), soft tissue ACLR grafts ( 29 ), and knee hyperextension and generalized laxity ( 63 , 68 ). Another population which merits consideration is high-level athletes.…”
Section: Lateral Extra-articular Augmentationmentioning
confidence: 99%
“…8,12,19,23 Moreover, associated injuries, such as meniscal, cartilage, or collateral ligament lesions, may result in an increased risk of early osteoarthritis 2,7,20,26,28,30 and/or graft failure. 3,9,16,24,25,28,29 Because specific injury patterns are associated with certain sports, a better understanding of sport-specific injury mechanisms may lead to more personalized and effective ACL injury prevention programs. 31 To the best of our knowledge, only a few studies have described the effect of sport-specific injury mechanisms on concomitant injuries during ACL rupture.…”
mentioning
confidence: 99%